2022
DOI: 10.1186/s12903-022-02295-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enterococcus faecalis OG1RF on human calvarial osteoblast apoptosis

Abstract: Background Enterococcus faecalis is a dominant pathogen in the root canals of teeth with persistent apical periodontitis (PAP), and osteoblast apoptosis contributes to imbalanced bone remodelling in PAP. Here, we investigated the effect of E. faecalis OG1RF on apoptosis in primary human calvarial osteoblasts. Specifically, the expression of apoptosis-related genes and the role of anti-apoptotic and pro-apoptotic members of the BCL-2 family were examined. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Recently, a polymerase chain reaction (PCR) array analysis of 84 apoptosis-related genes in E. faecalis -infected human calvarial osteoblasts revealed that Bcl-2 family members acted as regulators of osteoblast apoptosis. Therefore, Bcl-2 family members may be potential therapeutic targets for RAP [ 110 ]. Notably, utilising inhibitors targeting pyroptosis or necroptosis-related molecules may have a significant impact on the resolution of E. faecalis -induced RAP since it reduces pro-inflammatory cytokine release rather than just inhibits cell death.…”
Section: E Faecalis -Modulated Host Cell Responsesmentioning
confidence: 99%
“…Recently, a polymerase chain reaction (PCR) array analysis of 84 apoptosis-related genes in E. faecalis -infected human calvarial osteoblasts revealed that Bcl-2 family members acted as regulators of osteoblast apoptosis. Therefore, Bcl-2 family members may be potential therapeutic targets for RAP [ 110 ]. Notably, utilising inhibitors targeting pyroptosis or necroptosis-related molecules may have a significant impact on the resolution of E. faecalis -induced RAP since it reduces pro-inflammatory cytokine release rather than just inhibits cell death.…”
Section: E Faecalis -Modulated Host Cell Responsesmentioning
confidence: 99%